The prevalence of the technocratic model in obstetric care from the perspective of health professionals - Marli Therezinha Stein Backes; Karini Manhães de Carvalho; Larissa Nascimento Ribeiro; Tamiris Scoz Amorim; Evanguelia Kotzias Atherino dos Santos; Dirce Stein Backes (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to identify the reasons for the prevalence of the technocratic model in obstetric care from the perspective of health professionals. Methods: Grounded Theory. Study approved by two Research Ethics Committees and conducted by theoretical sampling, from July 2015 to June 2017. Twenty-nine interviews were conducted with health professionals from two maternity hospitals in the Southern Region of Brazil. Data collection and analysis was performed alternately; and analysis by open, axial, and selective coding/integration. Results: the technocratic model still persists because the assistance is performed in a mechanized way, centered on the professionals. There is a lack of systematization of care, and under-dimensioning of the nursing staff. Final Considerations: obstetric nurses need to review their performance in obstetric centers, the internal organization, the dimensioning of nursing professionals, and become protagonists of care. Investment in academic training/updating the knowledge of midwifery professionals, based on scientific evidence and user-centered care is necessary.